The History of Corona Virus, from Neanderthals to the Present Time: A Brief Review - Dariush D. Farhud; Mahsa Azari; Atefeh Mehrabi (Tehran University of Medical Sciences, 2022)
Contrary to popular belief, 2019 was not the first time humans were infected by the Coronavirus. Coronavirus is one of the oldest viruses on the earth. This article discusses the history of this virus from Neanderthal time so far. We have collected a variety of articles related to coronaviruses and the extent of their interaction with humans from the first time probably appeared on earth, given that this virus is one of the ancient viruses. By examining and following the footsteps of coronaviruses in different works of literature, we found that the first homo that was infected with the coronavirus was Neanderthal. Moreover, we realized that in addition to risk factors such as age and background diseases, genetic evolution also plays an essential role in the protection of the body against coronavirus. On the other hand, this virus has evolved throughout history gradually, the same as humans. The presence of disease in humans, in any period of history, causes changes in human quality of life. Therefore, paying attention to the background of ancient diseases reveals principal information about the complexity of pathogens.